To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
The GCF is 5b.
2a+5b isn't possible the answer is still 2a+5b.
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
The greatest common factor (GCF) of 15ab and 5b2 is 5b.
5b + 5b = 2 x 5b
To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
5(3a - 5b + 4)
The GCF is 5b.
2a+5b isn't possible the answer is still 2a+5b.
5b-15 = -10
15 = 5b
5b
5b-32
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
5b + 3 = 10 - 3 - 3 5b = 7 5b/5 7/5 b= 1.5 There you go !
(5b - 4)(5b + 4)